Reduced diversity of gut microbiota in two Aedes mosquitoes species in areas of recent invasion. Issue 1 (December 2018) - Rosso, Fausta; Tagliapietra, Valentina; Albanese, Davide; Pindo, Massimo; Baldacchino, Frédéric; Arnoldi, Daniele; Donati, Claudio; Rizzoli, Annapaola
Abstract Aedes mosquitoes are considered highly successful global invasive species and vectors of several pathogens of relevance for public health. Their midgut's microbiota can play an important role in affecting not only their vectorial competence but also their fitness, physiology, food digestion, metabolism, immunity and adaptation to new environmental conditions. Using high-throughput sequencing we compared the microbiota ofAedes albopictus collected in Italy with those reported in populations from France and Vietnam. We also analysedAedes koreicus gut microbiota for the first time. We found remarkable individual difference along with common bacterial taxa in both species.Ae. albopictus collected in Italy had a lower richness and a different composition of microbiota in respect to specimens collected in France and Vietnam. It also showed a core microbiota formed mainly of bacteria of the genusPseudomonas . Overall, the twoAedes species (Ae .albopictus andAe .koreicus ) collected in Italy, showed a large core microbiota with 75.98% of the identified Operational Taxonomic Units. Furthermore, Ae .albopictus had 2.5% prevalence ofWolbachia and 0.07% ofAsaia spp, whileAe .koreicus had 14.42% ofAsaia spp. and noWolbachia . This study provides new informations on the spatial variation of the midgut bacterial communities in mosquitoes of medical relevance within areas of recent invasion and provide the basis for further studies aimed at assessing the effects of such variation on vectorial capacity for a range of pathogens.